‘Who Touched Me?’ Embodied Witness as Public Theology - Wivell, Ruth (2023)
This article addresses how trauma might inform the way Mark’s account of the haemorrhaging woman is read, and what a Christology derived therefrom might offer to Christians who wish to witness to people’s traumatic and posttraumatic realities. If Christians and theologians are called to witness to others’ suffering and their attempts to make sense of it, then they need to be able to inhabit a space that draws forth stories of those disempowered and traumatized. In particular, this article explores these issues by addressing inter-related facets of Jesus the Christ in Mark 5:24–34 as he responds to the haemorrhaging woman and is involved in her healing. It is Jesus’s shift to witness – as he loses power and cognition – that brings about the hope of ongoing restoration of the woman’s body and spirit.
Keywords: Witness; Trauma; Public Theology; Haemorrhaging Woman; Feminist Theology; Christology